Cocoa Sector Expenditure and Revenue in Ghana - International Food Policy Research Institute; Ghana Cocoa Board (International Food Policy Research Institute, 2014)
The Cocoa Sector Expenditure and Revenue in Ghana dataset contains expenditure and revenue data from cocoa sector in Ghana. The dataset aggregates information from various sources including Food and Agriculture Organization (FAO), Ghana Cocoa Board (COCOBOD), and Producer Price Review Committee (PPRC). These data are available from 1996-2012.